The Management of Laboratory-Based Biology Learning (ASite Study at SMP Negeri 2 Magelang) - Lartono, Lartono (2011)
The objective of this research is to describe the readiness and interior design characteristic in the laboratory-based Science learning, teaching material in the laboratory-based biology learning, students' interaction in the laboratory based biology learning in SMP Negeri 2 Magelang. Type of this research is a qualitative research with ethnography approach. This research is limited on the management of laboratory-based Biology learning at SMP Negaeri 2 Magelang. The main data is from the informant such as the principal, the vice principal, teacher, other education officer, and formal documents. Data collection methods are observation, in-depth interview, and documentation. Data analysis in this research use reduction data, display data, and conclusion drawing/ verification data. Data validity used in this research is using triangulation data technique. The results of this research are: (1) the readiness characteristic of SMP Negeri 2 Magelang in the laboratory-base biology learning is in the new school year in 2010/2011 design the laboratory interior, painting the laboratory room, repairing laboratory water furniture, and setting the equipment and material of the laboratory; and preparing work program and administration of the Science laboratory among other laboratory organization structure, laboratory organization tasks, vision and mission of Science laboratory, inventory of laboratory equipments and materials (2) teaching material in the laboratory-based biology learning with the competence standard: (a) understanding the diversity of the creature; (b) understanding the interdependence of ecosystem; (c) understanding the various system in the human life; (d) understanding the system in the plant life; and (e) understanding the survival of the creature. The material given in SMP Negeri 2 Magelang related to the laboratory-based biology learning focused in the creature, this is due to the availability of equipment which is considered closest to students. (3) students' characteristic in the activity of laboratory-based biology learning at SMP Negeri 2 Magelang is observing, measuring and identifying object of life symptom as well as classifying the creature, discussing, concluding and preparing the practicum activity report. Students also discuss with their group related to preparing practicum activity plan that will be done with teacher, so the practicum activity can run well. The students hold discussion in the end of practicum activity to strengthen students' understanding of the concept learned, interpret and analyze data and make the conclusion.